Measuring material plastic response to cyclic loading in modern rail steels from a minimal number of twin-disc tests. (November 2021) - Tomlinson, K; Fletcher, DI; Lewis, R
Advances in rail materials from conventional rail steels to those with higher yield points and the potential of additively manufactured laser clad coatings to improve the durability of railway track components presents a new challenge in characterisation. Many of these new and novel materials have either limited test samples available or are more resistant to strain and therefore present challenges in characterisation. The method reported here uses twin disc tests to simulate cyclic loading experienced by rail steel in service. A sample from a single test condition is analysed, measuring the shear yield stress and the accumulated shear strain at multiple depths below the contact surface, from which a Shear Yield Stress – Plastic Shear Strain (SYS-PSS) relationship is extracted. Knowledge of the stress history of a rail sample is not required to apply the method and minimal samples are required, providing a technique which can be used on rail steel samples removed from service.